Meeting the Needs of Chinese International Students: Is There Anything We Can Learn From Their Home System? - Liu, Wei; Lin, Xiaobing (Journal of studies in international education, 2016)
Discussed in this article are the different governance models in international student services in Canadian and Chinese universities. Informing this study were 39 international student service providers from 38 top Chinese universities while interacting with their Canadian counterparts in a professional development program in Canada. The derived comparative data serve to show that a reactive decentralized model is used in international student services in Canada, while practiced in China is a more centralized proactive model. Although both models are rooted in their own social and cultural contexts, mutual learning is possible to some extent. The article ends with some discussion about possible ways Canadian universities can borrow from the Chinese system. (HoF/text adopted).